Born of betrayal - Kenyon, Sherrilyn, 1965- (Kenyon, Sherrilyn, 1965- League., 2015)
"Years ago, family loyalty caused Fain Hauk to give up everything he loved: His military career. His planet. His fiancée. Even his name. Now decades later, everything has changed. He's built a new life out of the ashes of his old, and he's vowed to never let anything threaten his loved ones again. But when old enemies align themselves with new ones, he's caught in the middle of a brutal war. And when fate throws his former fiancée back into his world and she has her own agenda that includes taking his head for what he did to her years ago, more than just his life is at stake. The fate of the Ichidian universe and that of his brothers-in-arms hangs in the balance. Winner take all. It's killed or be killed, and never has the battle been more fierce...Or more fun"--